FEATURES OF MOZZARELLA THAT WE DO NOT KNOW (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The economic and social development of our country, increasing the welfare of our people, as well as fully satisfying our people's demand for food, especially milk and milk products, are among the most important issues. Acceleration of milk production in many ways requires production processes to be carried out on the basis of intensive technology. Many products can be obtained by processing milk. Cheese ranks high among all dairy products due to its high level of nutrition and richness of substances. Regular consumption of mozzarella cheese is very beneficial for the human body.